A Study on Injury Issues & Body Mass Index (BMI) of Female Karate Players in South 24 Parganas, West Bengal - Das, Dr. Soma; Chakraborty, Bipul (European Journal of Life Safety and Stability (2660-9630), 2024)
The aim of this paper was to focus on injury issues among female karate players and how these issues are related with their age and body mass index (BMI). The study was done on twenty-six female players in the Baruipur and Subhash gram areas in South 24 Parganas in West Bengal. The stratified random sampling procedure was applied for the selection of the sample group.A prospective recording of the injuries resulting from Data on their demographic characteristics (Age and Weight), BMI were recorded by standard methods. A self -made questionnaire was used for survey on health issues. Results indicate ankle injury and bone injuries were most common along with the anxiety issue. Their age was found positively correlated with BMI value. However, the correlation of BMI with injuries and anxiety was positive but not statistically significant. This study is a novel attempt of its kind as no similar work on the population of female karate players in West Bengal was found in literature. The findings could improve the awareness of the players and coaches about the chances of injury during the sport practise.